Redesigning Primary Care in an Academic Medical Center: Lessons, Challenges, and Opportunities - Egede, Leonard E. (Postgrad Med, 2020)
PURPOSE: To evaluate patient access, provider productivity, and patient satisfaction during a 24-month redesign process of an academic medical center, which requires balance between clinical and educational missions. METHODS: A series of activities were conducted to optimize primary care across 17 attending physicians, 6 Advanced Practice Providers (APPs), and 39 residents. Patient access was defined as the next available appointment for either existing/established patients or new patients. Productivity was measured using panel sizes for each provider. Patient satisfaction was based on the Clinician and Group Consumer Assessment of Healthcare Providers and Systems (CGCAHPS). RESULTS: Despite decreasing clinical effort to allow faculty and APPs to participate in education and research, there was an overall increase in access for both new and established patients, and an increase the percent of each providers’ panel that was full from 78.89% in 2017 to 115.29% in 2019. When comparing panel sizes for the 11 faculty present before and after strategic changes, we found significant increase in both overall panel size, and actual to expected ratios between 2017 and 2019. In addition, throughout the time period, patient satisfaction remained high with no significant changes. CONCLUSIONS: While this project was limited to one site, the inclusion of a set of well-planned metrics, and tracking of processes over time can provide insight for ongoing primary care redesign efforts at similar sites seeking to balance the academic mission with clinical productivity and high patient satisfaction.